Customization and Personalization in Luxury Marketing : Understanding Consumer Perceptions and Industry Trends. - Hardiyanti, Widya (2024)
This thesis explores the role of evolving customization and personalization strategies in luxury marketing, focusing on customer experiences and industry professional insights. Using qualitative research methods, the study examines tangible personalization and customization experience (e.g.,monogramming and engraving). The findings of this study will not only enrich our understanding of the tools and strategies employed by luxury brands but will also provide valuable insights into the motivation, perceptions, challenges to appeal to future customers.